Stable Isotopes Analysis (Carbon and Nitrogen) in the Central Western Argentina Archaeology: A Review - Gil, Adolfo; Neme, Gustavo; Peralta, Eva A. (Ethnobiology Letters, 2025)
Stable isotopes analysis has become an essential part of the archaeological research agenda that engages ethnobiology. This paper reviews its impact in regional archaeological research focusing on the introduction of domesticated plants and their evolution in the human-environment system in Central Western Argentina (CWA). We emphasize the significance of stable isotopes in investigating the complex evolutionary history of maize adoption and agricultural practices within a dynamic Late Holocene boundary zone between farming and hunter-gathering. The 30-year history of archaeological isotopic research in CWA represents a dynamic history of old and new questions and methodologies, greater statistical sophistication and theoretical depth in its interpretation. Its impact, initially limited to reconstructing human diets, has now expanded significantly, providing powerful tools to model humans as part as a dynamic ecosystem.